In Silico Evaluation of Physalis angulata Secondary Metabolites as Potential QcrB Inhibitors in Mycobacterium tuberculosis and Mycobacterium bovis - Zahir Thoriq -; Lia Puspitasari; Lita Rakhma Yustinasari; Suryo Kuncorojakti; Tarshan Sharma Suresh (VITEK : Bidang Kedokteran Hewan, 2026)
Antimicrobial resistance in Mycobacterium tuberculosis and Mycobacterium bovis remains a major challenge in human and veterinary medicine, emphasizing the importance of identifying novel therapeutic compounds. This study aimed to predict the most promising secondary metabolite of Physalis angulata as a quinol–cytochrome c reductase subunit B (QcrB) inhibitor using an in silico approach. Sequence alignment of QcrB proteins from M. tuberculosis and M. bovis demonstrated complete sequence identity, indicating that compounds targeting QcrB in M. tuberculosis may exhibit comparable binding behavior toward QcrB in M. bovis. Among 51 identified metabolites, nine satisfied drug-likeness and safety criteria and underwent molecular docking analysis. Docking simulations predicted that four metabolites occupied the QcrB binding pocket, with withaphysanolide A exhibiting the most favorable interaction profile based on predicted binding free energy and correspondence with reference residues. Absorption, distribution, metabolism, excretion, and toxicity (ADMET) analysis predicted favorable pharmacokinetic and safety-related characteristics for withaphysanolide A. However, these findings should be interpreted in light of several limitations, including the use of rigid docking and the absence of molecular dynamics simulations. Collectively, the results suggest that withaphysanolide A may represent a promising QcrB inhibitor candidate for further investigation, although in vitro and in vivo validation remains necessary.